2017
DOI: 10.1182/blood-2016-07-730614
|View full text |Cite
|
Sign up to set email alerts
|

MUC1-mediated induction of myeloid-derived suppressor cells in patients with acute myeloid leukemia

Abstract: Myeloid-derived suppressor cells (MDSCs) play a critical role in promoting immune tolerance and disease growth. The mechanism by which tumor cells evoke the expansion of MDSCs in acute myeloid leukemia (AML) has not been well described. We have demonstrated that patients with AML exhibit increased presence of MDSCs in their peripheral blood, in comparison with normal controls. Cytogenetic studies demonstrated that MDSCs in patients with AML may be derived from leukemic or apparently normal progenitors. Engraft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 51 publications
8
118
0
1
Order By: Relevance
“…28 A more recent study demonstrated a higher frequency of MDSCs in the peripheral blood of AML patients and the expansion of MDSCs is driven by leukemia-derived extracellular vesicles. 29 In line with these findings, we observed an enhanced presence of monocytic MDSCs in the peripheral blood of AML patients. The number of MDSCs was significantly reduced in patients achieving complete remission after induction chemotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…28 A more recent study demonstrated a higher frequency of MDSCs in the peripheral blood of AML patients and the expansion of MDSCs is driven by leukemia-derived extracellular vesicles. 29 In line with these findings, we observed an enhanced presence of monocytic MDSCs in the peripheral blood of AML patients. The number of MDSCs was significantly reduced in patients achieving complete remission after induction chemotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, MUC1 silencing did not lead to change in cell viability as determined by annexin/PI analysis in MOLM-14 and THP-1 cells. 66 However, tumor cell proliferation was shown to be reduced in MOLM-14 CRISPR cells as determined by Ki67 analysis (Supplementary Figure 2D). …”
Section: Discussionmentioning
confidence: 96%
“…Myeloid‐derived suppressor cells (MDSCs) are a heterogeneous group of immature myeloid cells capable of potently suppressing the function of immune cells. Numbers of circulating MDSCs have been reported to be elevated in AML patients, thereby inhibiting the endogenous immune response and potentially hampering the function of CAR T cells . Thus, reducing the frequency of MDSCs could also prevent leukemic blasts from evading CAR T‐cell treatment.…”
Section: The Challenge Of Circumventing Immune Escapementioning
confidence: 99%
“…Numbers of circulating MDSCs have been reported to be elevated in AML patients, thereby inhibiting the endogenous immune response and potentially hampering the function of CAR T cells. 9 Thus, reducing the frequency of MDSCs could also prevent leukemic blasts from evading CAR T-cell treatment. Preclinical data suggest that administration of CD33/CD3 bispecific antibody (BiTe) can eliminate CD33-expressing MDSCs.…”
Section: The Challenge Of Circumventing Immune Escapementioning
confidence: 99%